(untitled) - Slade, Paul G. (Boca Raton, 2008)
Vacuum interrupters are the dominant technology for many circuit switching and protection devices, such as circuit breakers, reclosers, and contactors. Based on the author's nearly four decades of practical experience in the industry, Vacuum Interrupters: Design and Applications provides an in-depth discussion of vacuum interrupter design with an emphasis on the science behind it. This book highlights the ever-widening range of applications for vacuum interrupters, including those currently being developed by engineers. It also offers a qualitative explanation and rationale behind current design principles. In addition, each chapter includes an extensive list of references for further exploration.
Keywords: Vacuum switches,Electric circuit-breakers, Vacuum,Kỹ nghệ điện